IKTISYÂF FA'ÂLIYYAH THARÂIQ TA'LÎM AL-LUGHAH AL-'ARABIYYAH FÎ AL-MADRASAH AL-TSÂNAWIYAH - Shabari, Ahmad Yani ibn Imam (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
The aim of this research was to identify the usefulness of the methods of teaching Arabic - secondary school (Bahr al-Ulum High School in Tampa, Bras Gumbang, Eastern Java, Indonesia) as a model for making Arabic language as a means of communication between students in the light of modern trends in Arabic language learning. This is a theoretical descriptive research field. To reach our goal of this study, we designed a questionnaire and then conducted it on a sample of the teachers of the school. This study reached the conclusion that the method used in the school was selective, but the translation is used very intensively, and the intermediate language in teaching is the Indonesian language, and this is perhaps the main reason for the low communication skills of students because we cannot imagine that the students knew how to communicate in Arabic language, if the teachers themselves do not speak in the classroom.